Turkish-Israeli Relations in Crisis: Living with the Gordian Knot - Özcan, Gencer (Études helléniques / Hellenic Studies, 2012)
This article focuses on the deep crisis the Turkish-Israeli relations entered, in the wake of the deadly assault on May 31st previous year on the aid ﬂotilla led by the Turkish ship Mavi Marmara during which eight Turkish citizens and a Turkish-American died. Furthermore the article will attempt to highlight the reasons that led the current Justice and Development Party [JDP] government to downgrade relations with Israel, and argue that unless prevailing political perceptions of Israel are profoundly changed, it would be difcult to end the stalemate.